2009
DOI: 10.1371/journal.pone.0008119
|View full text |Cite
|
Sign up to set email alerts
|

Simplified, Enhanced Protein Purification Using an Inducible, Autoprocessing Enzyme Tag

Abstract: We introduce a new method for purifying recombinant proteins expressed in bacteria using a highly specific, inducible, self-cleaving protease tag. This tag is comprised of the Vibrio cholerae MARTX toxin cysteine protease domain (CPD), an autoprocessing enzyme that cleaves exclusively after a leucine residue within the target protein-CPD junction. Importantly, V. cholerae CPD is specifically activated by inositol hexakisphosphate (InsP6), a eukaryotic-specific small molecule that is absent from the bacterial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 19 publications
0
81
0
1
Order By: Relevance
“…Cloning, Expression, and Characterization of Endo-S2-cDNA sequence encoding Endo-S2 (38 -819) was cloned into a pET22b-CPD vector, which adds to the C terminus of the expressed protein the cysteine protease domain (CPD) of the Vibrio cholerae MARTX toxin and a ϫ10 histidine tag (35). We have recently reported that a high-level, soluble expression of Endo-F3 and its mutants could be achieved using this vector (32).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cloning, Expression, and Characterization of Endo-S2-cDNA sequence encoding Endo-S2 (38 -819) was cloned into a pET22b-CPD vector, which adds to the C terminus of the expressed protein the cysteine protease domain (CPD) of the Vibrio cholerae MARTX toxin and a ϫ10 histidine tag (35). We have recently reported that a high-level, soluble expression of Endo-F3 and its mutants could be achieved using this vector (32).…”
Section: Resultsmentioning
confidence: 99%
“…Site-directed Mutagenesis and Expression and Purification of Recombinant Endo-S2-cDNA encoding amino acids 38 -819 of Endo-S2 from S. pyogenes NZ131 (serotype M49) was amplified by PCR and cloned into the pCPD-Lasso vector (a pET22b-CPD derivative) (35). For saturation mutagenesis of the Asp-184 residue, a forward primer, 5Ј-CGTAAATTCGTGCT-CAATNNNAATATCTAGTCCATCGACACCACGATCA-GTT-3Ј, and a reverse primer, 5Ј-AACTGATCGTGGTGTCG-ATGGACTAGATATTNNNATTGAGCACGAATTTACG-3Ј, were used.…”
Section: Methodsmentioning
confidence: 99%
“…For Sen1 Hel expression, we used a fusion protein with a cleavable C‐terminal His tag coupled to Vibrio cholerae MARTX toxin cysteine protease domain (His 8 ‐CPD) (Shen et al , 2009). His 8 ‐CPD tagged Sen1 Hel (1,095–1,904) and its mutant derivatives were purified from Escherichia coli BL21 (DE3) STAR pRARE (Stratagene) cells grown in TB medium.…”
Section: Methodsmentioning
confidence: 99%
“…Wild-type full-length NES was previously cloned into the cysteine protease domain (CPD) fusion protein expression system developed by Shen et al and optimized by our lab (7,21). Loop deletion mutants were made through site-directed mutagenesis to remove hairpin loop 1 (residues 77 to 82) and hairpin loop 2 (residues 150 to 157) and replace each with a linker composed of one glycine and one serine.…”
Section: Methodsmentioning
confidence: 99%